(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
Three specimens of the man-of-war fish, Nomeus gronovii, from the Santa Marta and Cartagena areas (Colombian Caribbean) are presented as the first records of the species from the South American coasts over the Caribbean Sea.